Sorbent on the basis of Ti/Mn oxide and Co cyanoferrate for 90Sr and 137Cs selective removal - Maltseva, Tetyana; Palchik, Alexey; Bondarenko, German (My University, 2018)
The complex oxides of MxMn1-xO2•nH2O composition, (M-Zr, Ti, Sn) have been synthesized. Their surface was modified with phosphoric acid. phosphoric-molybdic acid and cobalt hexacyanoferrate. The sorption isotherms of Sr2+, Cs+ ions, as well as isotherms of sorption-desorption of such radionuclides as 90Sr and 137Cs were obtained. It was found that the most suitable sorbents for Sr2+ removal are MxMn1-xO2•nH2O complex oxides. ZrO2 modified by phosphate and molybdophosphate anions is effective towards Cs+. The sorbent consisting of titanium dioxide and cobalt hexacyanoferrate can be recommended for extraction of both Sr2+ and Cs+ ions.
Keywords: sorbent; composite; double oxides; hexacyanoferrate; strontium; cesium; сорбент; композит; подвійні оксиди; гексацианоферат; стронцій; цезій; двойные оксиды; гексацианоферрат; стронций; цезий